Pengembangan Pariwisata Ekonomi Kreatif Desa Wisata Berbasis Budaya Sebagai Niche Market Destination (Studi Kasus Pengembangan Desa Wisata di Kabupaten Sleman) - Lastiani Warih Wulandari (Jurnal Aplikasi Bisnis, 2017)
This study purposed to describe tourism profile as a part of destination tourism. Cultural differences, together with asymmetry of the fruquent and transitory tourist-host contact, are the most important factor which influence interaction difficulties between tourist and host. Therefore, understanding of cross cultural tourist host contact and influence of the cultural background of tourist and host is the key feature for identification of the cultural potential for tourist-host interaction and the effect of this interaction on the overall tourist holiday satisfaction.